2017
DOI: 10.1038/cmi.2016.70
|View full text |Cite
|
Sign up to set email alerts
|

Regnase-1, a rapid response ribonuclease regulating inflammation and stress responses

Abstract: RNA-binding proteins (RBPs) are central players in post-transcriptional regulation and immune homeostasis. The ribonuclease and RBP Regnase-1 exerts critical roles in both immune cells and non-immune cells. Its expression is rapidly induced under diverse conditions including microbial infections, treatment with inflammatory cytokines and chemical or mechanical stimulation. Regnase-1 activation is transient and is subject to negative feedback mechanisms including proteasome-mediated degradation or mucosa-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 104 publications
(162 reference statements)
3
47
0
2
Order By: Relevance
“…A Proteína Induzida por Proteína Quimiotática de Monócito 1 (MCPIP1), também conhecida como regnase-1, foi descoberta a partir da expressão em monócitos periféricos tratados com Proteína Quimiotática Monocitária 1 (MCP-1) (38). Estudos indicaram que a mesma tem quatro domínios: um domínio N-terminal (NTD), um domínio como o N-terminal da PilT (PIN), um domínio finger de zinco (ZF) e um domínio C-terminal (CTD), nos quais os domínios PIN e DTN atuam na atividade enzimática (39). O MCPIP1 inibe a ativação de macrófagos e a produção de citocinas inflamatórias, como o TNFα, IL-1β, IL-6, MCP-1 e as vias inflamatórias do NF-kB.…”
Section: Medline (N=176)unclassified
“…A Proteína Induzida por Proteína Quimiotática de Monócito 1 (MCPIP1), também conhecida como regnase-1, foi descoberta a partir da expressão em monócitos periféricos tratados com Proteína Quimiotática Monocitária 1 (MCP-1) (38). Estudos indicaram que a mesma tem quatro domínios: um domínio N-terminal (NTD), um domínio como o N-terminal da PilT (PIN), um domínio finger de zinco (ZF) e um domínio C-terminal (CTD), nos quais os domínios PIN e DTN atuam na atividade enzimática (39). O MCPIP1 inibe a ativação de macrófagos e a produção de citocinas inflamatórias, como o TNFα, IL-1β, IL-6, MCP-1 e as vias inflamatórias do NF-kB.…”
Section: Medline (N=176)unclassified
“…Among the examined RNases, our initial screening analysis revealed that Regnase-1 (a zinc nger CCCH-type containing 12A encoded by Zc3h12a in mouse) was exclusively up-regulated in chondrocytes stimulated with OA-associated catabolic factors. Regnase-1, which is also known as MCPIP1 (monocyte chemotactic protein-induced protein 1), is an endonuclease that destabilizes various target mRNAs by recognizing a stem-loop structure within their 3´-UTRs [11,12]. Regnase-1 is known to play diverse functions in different cell types, such as mitigating in ammation by down-regulating the IL-6 and IL-12B mRNAs in monocytes [11]; restricting T cell activation by targeting the c-Rel, Ox40, and IL-2 mRNAs in T cells [13,14]; and promoting cancer cell apoptosis by regulating mRNAs of Bcl2L1, Bcl2A1, RelB, and Bcl3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, MALT1 functions as a scaffold protein, leading to TRAF6-dependent NF-rB activation [27]. Second, MALT1 functions as a cysteine paracaspase, which catalytically processes the cleavage of negative regulators of NF-rB, such as RelB, A20, and cylindromatosis (CYLD), fueling NF-rB activation [28][29][30][31]. Based on the finding that MALT1 paracaspase activity is required for immune cell activation and proliferation, researchers have hypothesized that MALT1 is a promising therapeutic target for autoimmunity and cancer [32].…”
Section: Introductionmentioning
confidence: 99%